The effect of ablation settings on lesion characteristics with DiamondTemp ablation system: An ex vivo experiment - Takehiro Nomura; Manabu Maeda; Daiki Kumazawa; Yosuke Mizuno; Kosuke Onodera; Shigeru Toyoda; Kennosuke Yamashita (Journal of Arrhythmia, 2024)
Abstract Introduction Creating large lesion in ablations using the DiamondTemp (DTA) ablation system may reduce the frequency of arrhythmia recurrence and allow the treatment of ventricular arrhythmias. Therefore, this study aimed to investigate whether power, application time, contact force (CF), and contact angle affect lesion formation in the ventricles. Methods Ablations were delivered to porcine myocardial preps to evaluate the lesion characteristics. Ablations were conducted with a maximum power of 50 W, target temperature of 58°C, CF of 10, 20, or 30 g, and contact angle between the catheter tip and tissue. The ablation durations were 15, 30, 60 s, 15 s × 2, or 30 s × 2. Results Steam pops occurred only in cases with perpendicular contact. The lesion depth was larger in all settings in the perpendicular orientation than in the parallel orientation. The temperatures were lower in all settings in the perpendicular orientation than in the parallel orientation. The lesions became larger as CF increased with perpendicular contact and duration of ≥30 s. The longer application time resulted in larger surface area, depth, and volume of the lesion. Lesion depth was greater with single application of 30 and 60 s than with 15 s × 2 and 30 s × 2, respectively. Conclusion It is important to perform a single prolonged application as much as possible to create deeper lesions. Parallel contact with the tissue should be maintained to take advantage of the temperature sensor's capabilities to avoid pop phenomenon.